Identification of Novel Surface-Exposed Proteins of Rickettsia rickettsii by Affinity Purification and Proteomics - Gong, Wenping (Public Library of Science, 2014)
Rickettsia rickettsii, the causative agent of Rocky Mountain spotted fever, is the most pathogenic member among Rickettsia spp. Surface-exposed proteins (SEPs) of R. rickettsii may play important roles in its pathogenesis or immunity. In this study, R. rickettsii organisms were surface-labeled with sulfo-NHS-SS-biotin and the labeled proteins were affinity-purified with streptavidin. The isolated proteins were separated by two-dimensional electrophoresis, and 10 proteins were identified among 23 protein spots by electrospray ionization tandem mass spectrometry. Five (OmpA, OmpB, GroEL, GroES, and a DNA-binding protein) of the 10 proteins were previously characterized as surface proteins of R. rickettsii. Another 5 proteins (Adr1, Adr2, OmpW, Porin_4, and TolC) were first recognized as SEPs of R. rickettsii herein. The genes encoding the 5 novel SEPs were expressed in Escherichia coli cells, resulting in 5 recombinant SEPs (rSEPs), which were used to immunize mice. After challenge with viable R. rickettsii cells, the rickettsial load in the spleen, liver, or lung of mice immunized with rAdr2 and in the lungs of mice immunized with other rSEPs excluding rTolC was significantly lower than in mice that were mock-immunized with PBS. The in vitro neutralization test revealed that sera from mice immunized with rAdr1, rAdr2, or rOmpW reduced R. rickettsii adherence to and invasion of vascular endothelial cells. The immuno-electron microscopic assay clearly showed that the novel SEPs were located in the outer and/or inner membrane of R. rickettsii. Altogether, the 5 novel SEPs identified herein might be involved in the interaction of R. rickettsii with vascular endothelial cells, and all of them except TolC were protective antigens.